Centromere protein F and survivin are associated with high risk and a poor prognosis in colorectal gastrointestinal stromal tumours. Issue 9 (25th May 2011) - Chen, Wen-Bin; Cheng, Xiao-Bin; Ding, Wei; Wang, Yang-Jing; Chen, Dong; Wang, Jin-Hai; Fei, Ru-Shan
Abstract : Aims: Colorectal gastrointestinal stromal tumours (GISTs) are considered to be tumours with a relatively poor prognosis. Few reports have been performed to investigate the mechanisms behind their malignant behaviour and to identify new therapeutic strategies for their treatment. The authors conducted this study to explore potential targets for the treatment of colorectal GISTs (CRGISTs). Methods: In the current study, the authors focused on centromere protein F and survivin, two markers that are known to affect the malignant behaviour of other tumours. Expression of centromere protein F and survivin was detected through the immunohistochemical staining of paraffin-embedded tumour tissues and then scored. The relationship between the expression of the two markers and their clinical parameters was analysed. Associated Survival analysis was available based on follow-up information. Results: The authors demonstrated for the first time that centromere protein F and survivin expression were significantly associated with high risk and a poor prognosis (p<0.05) in CRGISTs. The authors also found that centromere protein F expression was more prevalent in males (p=0.002). Conclusions: The results suggest that centromere protein F and survivin are malignant behaviour markers for CRGISTs. The expression of centromere protein F or survivin points to a poor clinical outcome. Interfering with centromere protein F and/or survivin expression might be a potentially therapeutic strategy for treating malignant CRGISTs.